Assessment of the anticonvulsant activity of pyrazolo[1,5-a][1,3,5]triazines obtained by synthesis (2014)
Giving that the pyrazolo[1,5-a][1,3,5]triazine system is a potential source of pharmacological agents for treatment of central nervous system disorders this work was aimed to asses anticonvulsant and acute neurotoxic effects of six molecules obtained by synthesis, using experimental models in mice. A series of six pyrazolo[1,5-a] [1,3,5]triazines (EAC-21, EAC-31, EAC-33, MH4a, MH4b1 and MH4c) obtained by one-step reaction from S,S-diethyl aroyl-/hetaroylimidodithiocarbonates and 5-aminopyrazoles were screened in vivo (300 mg/kg, v.o.) for their anticonvulsant activity in the maximal electroshock (MES) test in ICR mice and for acute toxicity in the rota-rod and wiring test. The structures of the obtained compounds were unambiguously established by IR, 1H and 13C-NMR spectroscopic techniques, COSY 1H-1H, hsqc and hmbc experiments, mass spectrometry and elemental analyses. Results shown that only MH4b1 showed protection against MES (p and lt; 0.05) and was devoid of gross neurotoxicity signs. Therefore, MH4b1 was chosen for additional anticonvulsant screening against MES, pentylenetetrazole, picrotoxin, strychnine and 6 Hz psychomotor seizure model, in a dose dependent manner (50, 150, 300 mg/kg, v.o.). MH4b1 also protected against 6 Hz seizure test ( and gt; 150 mg/kg, v.o.). These data suggest that MH4b1 could be a source for anticonvulsant pyrazolo[1,5-a][1,3,5]triazine analogs potentially useful against tonic clonic and refractory seizures.